PL-7 Antisynthetase Syndrome in Association with Sjögren’s, Systemic Lupus Erythematosus, and Rheumatoid Arthritis - Mehrin Jawaid; Yael Ross; Mohammad Kamran (Case Reports in Rheumatology)
We present a rare case of PL-7 antisynthetase syndrome (ASS) in association with Sjögren’s, systemic lupus erythematosus (SLE), and seropositive rheumatoid arthritis (RA). Initially, the patient was diagnosed with Sjögren’s followed by Sjögren’s/SLE overlap and then Sjögren’s/SLE/RA overlap. She was eventually diagnosed with Sjögren’s/SLE/RA overlap with PL-7 ASS with interstitial lung disease (ILD). ILD was discovered after complaints of pleuritic chest pain with subsequent workup with coronary computed tomography (CT) revealing pulmonary fibrosis. This case demonstrates the ambiguity with which symptoms of ASS can present; given the high respiratory morbidity and mortality of ASS especially in non-Jo-1 patients, those who present with Raynaud’s, myositis, or joint pain, whether together or in isolation, should be assessed for presence of additional features of ASS and potentially undergo testing for ASS antibodies if appropriate.